Pengaruh Harapan Pendapatan, Penggunaan Media Sosial dan Literasi Digital Terhadap Minat Berwirausaha Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang - Fatimah, Sitti; Askandar, Noor Shodiq; Mustapita, Arini Fitria (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This research aims to determine the influence of income expectations, use of social media and digital literacy on increasing interest in entrepreneurship. The object of this research is Economics and Business students at the Islamic University of Malang with a sample size of 82 students who have taken entrepreneurship courses and do not yet have a business. The sampling technique used was purposive sampling. Data collection techniques use questionnaires and data analysis tools. This research uses a quantitative approach because the data is obtained in the form of numbers. Based on the results of research analysis, income expectations have a positive and significant effect on interest in entrepreneurship. The use of social media has a positive and significant effect on interest in entrepreneurship. and digital literacy has a positive and significant effect on interest in entrepreneurship. Keywords: Income Expectations, Use Of Social Media, Digital Literacy And Interest In Entrepreneurship.